Mechanisms, Diagnosis and Treatment of Bone Metastases - Jozef Ban (MDPI AG, 2021)
Bone and bone marrow are among the most frequent metastatic sites of cancer. The occurrence of bone metastasis is frequently associated with a dismal disease outcome. The prevention and therapy of bone metastases is a priority in the treatment of cancer patients. However, current therapeutic options for patients with bone metastatic disease are limited in efficacy and associated with increased morbidity. Therefore, most current therapies are mainly palliative in nature. A better understanding of the underlying molecular pathways of the bone metastatic process is warranted to develop novel, well-tolerated and more successful treatments for a significant improvement of patients’ quality of life and disease outcome. In this review, we provide comparative mechanistic insights into the bone metastatic process of various solid tumors, including pediatric cancers. We also highlight current and innovative approaches to biologically targeted therapy and immunotherapy. In particular, we discuss the role of the bone marrow microenvironment in the attraction, homing, dormancy and outgrowth of metastatic tumor cells and the ensuing therapeutic implications. Multiple signaling pathways have been described to contribute to metastatic spread to the bone of specific cancer entities, with most knowledge derived from the study of breast and prostate cancer. However, it is likely that similar mechanisms are involved in different types of cancer, including multiple myeloma, primary bone sarcomas and neuroblastoma. The metastatic rate-limiting interaction of tumor cells with the various cellular and noncellular components of the bone-marrow niche provides attractive therapeutic targets, which are already partially exploited by novel promising immunotherapies.